Recent Advancements in Chalcogenides for Electrochemical Energy Storage Applications - Mensah-Darkwa, Kwadwo; Nframah Ampong, Daniel; Agyekum, Emmanuel; de Souza, Felipe M.; Gupta, Ram K. (Energies (Basel), 2022)
Energy storage has become increasingly important as a study area in recent decades. A growing number of academics are focusing their attention on developing and researching innovative materials for use in energy storage systems to promote sustainable development goals. This is due to the finite supply of traditional energy sources, such as oil, coal, and natural gas, and escalating regional tensions. Because of these issues, sustainable renewable energy sources have been touted as an alternative to nonrenewable fuels. Deployment of renewable energy sources requires efficient and reliable energy storage devices due to their intermittent nature. High-performance electrochemical energy storage technologies with high power and energy densities are heralded to be the next-generation storage devices. Transition metal chalcogenides (TMCs) have sparked interest among electrode materials because of their intriguing electrochemical properties. Researchers have revealed a variety of modifications to improve their electrochemical performance in energy storage. However, a stronger link between the type of change and the resulting electrochemical performance is still desired. This review examines the synthesis of chalcogenides for electrochemical energy storage devices, their limitations, and the importance of the modification method, followed by a detailed discussion of several modification procedures and how they have helped to improve their electrochemical performance. We also discussed chalcogenides and their composites in batteries and supercapacitors applications. Furthermore, this review discusses the subject’s current challenges as well as potential future opportunities.